Factores estresantes y trastorno de ansiedad en un estudiante - Ramos Veintimilla, Sabrina Jamiled (2019)
The present research work on stressors and anxiety disorder in a student attending the psychological department of the Technical University of Babahoyo, the same as part of the current conception of academic requirements, a high level of autonomy, flexibility and security of itself, it allowed to show and clarify how stress can significantly affect the mental health of the individual, so that it must be treated by a professional in the area. However, this work will seek to reinforce knowledge on how to identify stressors and, in turn, how it influences the development of anxiety disorder, thus being able to use the most appropriate techniques to reduce or stop unwanted behaviors associated with said disorder, together To the Cognitive Behavioral Therapy which has given good results in this type of pathologies, it will be sought to give the student to learn to understand how their thoughts contribute to the psychophysiological symptoms, together with the best techniques of coping with the problem